Analisis Kesiapan Kebutuhan Infrastruktur Replikasi Basis Data pada Sekolah Musik Indonesia Solo - Willy Sudiarto Raharjo; Gani Indriyanta; Amsal Maestro (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
Sekolah Musik Indonesia (SMI) Solo is the center of SMI which has internal data using web-based application at appssmi.com site with SQL Server database and has not been backed up regularly. Database replication is a technique for copying and distributing data and database objects from one database to another and implementing synchronization so data consistency can be guaranteed. Replication can be implemented to the cloud by requiring Internet access. The main concern in SMI Solo was the quality access of the Internet connection and also infrastructure used in SMI Solo. The purpose of this research is to analyze the readiness of data replication infrastructure needs at SMI Solo. The results of the analysis are then used as the basis for making recommendations and design of information technology architecture in the implementation of SMI database replication. We concluded that the infrastructure owned by SMI Solo is sufficient to be used for database replication. This is demonstrated by the very satisfactory performance of the SMI Solo server network with 3.85 Mbps download throughput, 3.49 Mbps upload throughput, 0% packet loss, 25.88 ms delay, and 0.09 ms jitter. On database replication performance thorough test scenarios, average performance on snapshot replication is using for CPU 4.78%, DTU 5.94%, I/O 0.06% and log data I/O 5.25%. The average performance on transactional replication is CPU 0.09%, DTU 0.09%, data I/O 0%, and log I/O 0.04%. Some of the challenges in developing database replication infrastructure to be implemented in all SMI’s can run efficiently if each SMI has a local server and Internet network albeit with unstable throughput. Index Terms—Network Performance, Replication, Snapshot, Transactional